WE SUPPORT YOU: ACADEMIC PERFORMANCE AND SPORTS INVOLVEMENT AMONG UNIVERSITY STUDENTATHLETES - Patricia Pawa Pitil; Siti Maisarah Binti Azharin (Journal of Islamic, Social, Economics and Development, 2021)
One of the misconceptions about the university student-athletes is that they may not be capable to strive in academic performance towards academic excellence. This has become a stigma to those who are actively involved in sports. Correspondingly, the challenge of balancing academic standards with athletic competitiveness is not new. Therefore, this study aimed to assess the student-athletes from UiTM Sarawak (N=168) on the factors of the surrounding environment (support system) affecting sports involvement, and the perceived health condition in relation to academic performance (GPA). The data were gathered using the survey method where the questionnaire was distributed through an online platform. The results indicated that there was no significant relationship between GPA and the perceived health condition, and the support system (p > .05). For gender comparison, there was a significant difference in the perceived health condition (p <.05), but not in the support system (p > .05). Conclusively, the student-athletes has a good health condition level, with females being perceived to be at a higher level, and have great support from the environment in their sports career; where the academic achievements are concerned, regardless of the gender, the studentathletes are in good hands. It is recommended that the supports that are given to these studentathletes be maintained and to promote sports participation to the non-athletes.